2021
DOI: 10.22545/2021/00146
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic in Brazil: what is happening on the front line

Abstract: Knowledge about a disease, regardless of its etiology, passes through several spheres and the impact on health is known to be only the most obvious. The pandemic COVID-19, a disease caused by the SARS-CoV2 virus, has proved the resilience of communities around the world, especially in countries underprepared in terms of a variety of aspects such as infrastructure, technology and education. One of the largest economies in the world, Brazil as an emerging country has faced this great challenge. The number of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The severity of the crisis in Brazil was caused by reasons, including the country's enormous population, socioeconomic differences, difficulties implementing broad testing, and political conflicts that affected pandemic response plans. Prado et al [19] investigated and explained the effects of COVID-19 in Brazil, highlighting the historic economic collapse as the worst in the nation's history. The analysis confirmed that unemployment rates surged to 12.8%, leaving a startling 12 million unemployed people.…”
Section: Statistical Data and Analysis (Countries)mentioning
confidence: 99%
“…The severity of the crisis in Brazil was caused by reasons, including the country's enormous population, socioeconomic differences, difficulties implementing broad testing, and political conflicts that affected pandemic response plans. Prado et al [19] investigated and explained the effects of COVID-19 in Brazil, highlighting the historic economic collapse as the worst in the nation's history. The analysis confirmed that unemployment rates surged to 12.8%, leaving a startling 12 million unemployed people.…”
Section: Statistical Data and Analysis (Countries)mentioning
confidence: 99%